Niat Pembelian Kendaraan Listrik dengan Faktor Pendukung Harga, Sikap, Norma Subjektif, dan Kontrol Perilaku - Bernando, Franky Okto; Ray, Erick Lauren Ray (JURNAL ILMIAH MANAJEMEN & BISNIS, 2024)
Purpose – The objective of this study is to ascertain consumers' interest in purchasing electric vehicles by examining the correlation between the consumer purchase intention variable and the independent variables, attitude, subjective norm, perceived behavioural control, and price sensitivity as moderating factors.Methodology – The type of research carried out in this research is causal associative research with quantitative techniques. The population of this study are vehicle users using fuel oil in the JABODETABEK area and who do not yet own an electric vehicle. The sample in this study was 119 car users who use oil fuel. Data processing uses SmartPLS software to measure research data using the Partial Least Square (PLS) method.Findings – The study's findings indicate that although subjective norms have no bearing on customer purchase intention, attitude, perceived behavioural control, and price sensitivity do. The association between price sensitivity and subjective norms is also influenced, although it is unaffected by the relationship between attitude, perceived behavioural control, and consumer purchase intention.Originality/Novelty – This research model uses the price sensitivity variable as an intervening variable for consumer purchase intention for electric vehicles among oil-fueled vehicle users who have never used an electric car in the Jabodetabek area (Indonesia).